Surface engineering induced superstructure Ta2O5−x mesocrystals for enhanced visible light photocatalytic antibiotic degradation - Tang, Yanting; Huang, Jielin; Liu, Shuaifei; Xiang, Dandan; Ma, Xinqi; Yu, Xin; Li, Mingxue; Guo, Quanhui (Journal of colloid and interface science, 2021)
[Display omitted] •Surface engineered Ta2O5−x mesocrystals were synthesized.•The sample showed enhanced photocatalytic performance.•Alkali modifications induced increased surface areas and surface hydroxyl groups.•Possible degraded pathways and mechanism were proposed. Mesocrystals are types of fascinating multifunctional materials in fabricating rapid charge transport pathways, and surface engineering could be considered as a significant influencing factor in boosting charge separation for efficient photocatalytic application. In this work, surface engineered Ta2O5−x mesocrystals were synthesized by facile alkali treatment strategy for enhanced visible light photocatalytic tetracycline degradation. The highly enhanced photocatalytic activity could be attributed to the highly increased surface areas and surface hydroxyl groups to compare with those of commercial Ta2O5 and pristine Ta2O5−x mesocrystals, which could provide more surface reactive sites and high electron density center for trapping photo-generated holes. Besides, possible tetracycline transformation pathways over surface engineered Ta2O5−x mesocrystals and visible light photocatalytic mechanism were also proposed in this work. Current work also provides a facile strategy for regulating surface property of ultrawide bandgaps semiconductors for enhanced visible light photocatalytic performance.